HUBUNGAN SOSIAL ANTAR PEDAGANG BARANG HARIAN DI PASAR INPRES BANGKINANG - Remitha "; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted at the Inpres Bangkinang Market Kampar regency with problems: (1) What forms of social relations between traders in the daily goods Inpres Bangkinang Market?, (2) What factors are driving competition between traders in the daily goods Inpres Bangkinang Market. The purpose of this study was to determine the shape of social relations between traders in the daily goods as well as the Inpres Bangkinang Market To determine what factors are driving competition between traders in the daily goods Inpres Bangkinang Market. This research is a qualitative descriptive study population were 17 merchants using census method. To gather data, researchers used the method of observation, interviews and documentation of the respondents and the parties concerned. From the results of this study concluded that social relations Shape Inpres Market traders daily in Bangkinang is in the form of cooperation, accommodation and competition as well as the trader uses the principles of their own interests. But there is no occurrence of any conflict or dispute (conflict). But there are traders who have disharmony social relationships with other traders. Then factor that encourages competition among traders is the factor (1) the local economy, because if the local economy is low then sales decreased, (2) factors lies the store will also affect, because if the location of the store is not located, so consumers find it easy find and not too far to walk, (3) the service factor, because if satisfactory service consumers so that consumers will always remember and are interested in buying, (4) factors lies the goods traded, consumers are interested in buying when the consumer sees what one wants to buy, (5) the quality factor goods, if the goods were traded good, then consumers will become loyal customers to buy daily items needed and (6) open and close the store in accordance with market conditions, the faster the more revenue is opened and vice versa.Keywords: Social Relations, Dealer, Market